2020
DOI: 10.3389/fpsyg.2020.00929
|View full text |Cite
|
Sign up to set email alerts
|

Future-Oriented Happiness: Its Nature and Role in Consumer Decision-Making for New Products

Abstract: Cognitive evaluations only partially explain the consumer purchasing patterns, especially when consumers approach a product for the first time. In such an encounter, consumers anticipate the emotions they might experience as a result of their decision, as they cannot realistically evaluate product performances. The work investigates the nature and the influence of these future-oriented emotions, namely anticipated and anticipatory happiness, in the first encounter with new products. Through a first laboratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 79 publications
(152 reference statements)
0
10
0
Order By: Relevance
“…According to these results, where a significant relationship has been found between the two dimensions of this study, the model proposed here may constitute the way to design future management models based on brand orientation and happiness management (Bettiga and Lamberti, 2020). On the one hand, it can be achieved by constructing responsible, happy, creative and sustainable production models (González-Mansilla et al, 2019) and moreover, on the other hand, with the existence of a significant volume of professional managers involved in the belief that the corporate happiness of organisations is a strong differentiating element of their brand concerning their competitors (Cuesta-Valiño et al, 2020b).…”
Section: Discussionmentioning
confidence: 54%
“…According to these results, where a significant relationship has been found between the two dimensions of this study, the model proposed here may constitute the way to design future management models based on brand orientation and happiness management (Bettiga and Lamberti, 2020). On the one hand, it can be achieved by constructing responsible, happy, creative and sustainable production models (González-Mansilla et al, 2019) and moreover, on the other hand, with the existence of a significant volume of professional managers involved in the belief that the corporate happiness of organisations is a strong differentiating element of their brand concerning their competitors (Cuesta-Valiño et al, 2020b).…”
Section: Discussionmentioning
confidence: 54%
“…Taking into account the results of the sentiment analysis, it can be concluded that people have mixed sentiments (i.e., positive and negative) about sustainable consumption. A significant body of research shows that emotions play a crucial role in consumer behavior, including behavioral consumption patterns [141][142][143][144]. Research has also been carried out on the specific emotions (e.g., fear, guilt, joy, and pride) that shape sustainable consumption [31,145,146], including the impact of emotions on sustainable consumption in the time of the COVID-19 pandemic [21,147,148].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, anticipated emotions broadly involve two dimensions: positive anticipated emotions and negative anticipated emotions ( Song and Qu, 2017 ; Ahmed and Ting, 2020 ), which are distinguishable and useful for understanding consumer reaction or behavioral intention ( Babin and Attaway, 2000 ; Bagozzi et al, 2016 ). Early studies on anticipated emotions have shown that negative affective reactions in the forms of anticipated regret have a stronger effect than positive anticipated emotions on behavioral change ( Abraham and Sheeran, 2004 ; Conner et al, 2013 ; Bettiga and Lamberti, 2020 ). To affect purchasing decisions, both positive and negative anticipated emotions can be separated by motivating purchase and motivating non-purchase [ Bagozzi et al, 2016 ; i.e., positive anticipated emotions to purchase (situation 1), negative anticipated emotions to purchase (situation 2), positive anticipated emotions to non-purchase (situation 3), and negative anticipated emotions to non-purchase (situation 4)].…”
Section: Literature Reviewmentioning
confidence: 99%